PENGEMBANGAN LUDO WORD GAME SEBAGAI MEDIA PEMBELAJARAN PADA MATERI HIDROKARBON KELAS XI SMA - Salsabila Sari Badri, Iswendi (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The purpose of this research was to produce Ludo Word Game (LWG) chemistryas a learning media in hydrocarbon of high school class XI which was valid andpractical. The type of research was Research and Development (R D) with 4-D modelsnamely (1) define, (2) design, (3) develop, and (4) disseminate. This study examined thelevel of validity and practicality of the product. The instruments used were validity andpracticality questionnaires. Data collection techniques were carried out by distributingquestionnaires and analyzed using the Cohen Kappa formula. Chemical LWG wasvalidated by three Chemistry lecturers at FMIPA UNP and two chemistry teachers fromSMAN 2 Gunung Talang. The determination of the practicality level was carried out bytwo chemistry teachers at SMAN 2 Gunung Talang and 30 students in class XI MIPA 2of SMAN 2 Gunung Talang. From the data analysis, it was found that the chemicalLWG as a media of learning in hydrocarbon had a validity of 0.83 with a very highvalidity category and the practicality value of the teacher was 0.92 and the studentswere 0.89 with a very high practicality category. This data shows that the chemicalLWG as a media of learning that was developed can be used as a learning media forhydrocarbon in class XI SMA.Keywords: Chemical LWG, learning media, Hydrocarbon, Research and Development,4-D models.